Near-Infrared Luciferase Complementation Assay with Enhanced Bioluminescence for Studying Protein–Protein Interactions and Drug Evaluation Under Physiological Conditions - Chen, Minghai; Yan, Chuang; Qin, Fujun; Zhang, Xian-En (Analytical chemistry (Washington), 2022)
Identification of protein–protein interactions (PPIs) that occur in various cellular processes helps to reveal their potential molecular mechanisms, and there is still an urgent need to develop the assays to explore PPIs in living subjects. Here, we reported a near-infrared split luciferase complementation assay (SLCA) with enhanced bioluminescence produced by cleaving a luciferase, Akaluc, for exploring and visualizing PPIs in living cells and live mice. Compared with the previously developed and widely used red SLCA based on split firefly luciferase (Fluc-SLCA), the signal intensities for PPI recognition in living cells and live mice of the Akaluc-SLCA increased by ∼3.79-fold and ∼18.06-fold in the measured condition, respectively. Additionally, the interactions between the nucleocapsid protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and cellular RNA processing proteins were identified, and the drug evaluation assays were also performed in living cells using Akaluc-SLCA. This study provides a new tool in the near-infrared region for the identification of PPIs in living cells and in vivo and new information for the understanding and treatment of SARS-CoV-2.